Peran dan Tanggung Jawab Notaris Berkaitan Dengan Pelaksanaan Corporate Social Responsibility Oleh Perseroan Terbatas - Desak Made Chyntia Dewi; Ayu Putu Laksmi Danyathi (Fakultas Hukum, Universitas Warmadewa, 2025)
Corporate Social Responsibility (CSR) is a legal obligation that must be implemented by every Limited Liability Company (PT) engaged in or related to natural resource management, as stipulated in Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies (UUPT) and Article 15(b) of Law Number 25 of 2007 concerning Investment (UUPM). The implementation of CSR represents a company’s social and environmental responsibility in supporting sustainable economic development. However, in practice, there remains a gap between normative regulation and its implementation, particularly regarding corporate compliance and the clarity of legal sanctions for violations. This study aims to analyze the legal framework governing CSR implementation by PTs and to and to analyze the notary’s role and legal responsibility in connection with the implementation of Corporate Social Responsibility (CSR) by Limited Liability Companies. The research employs a normative juridical method with statutory and conceptual approaches based on the provisions of the UUPT, UUPM, UUJN, and relevant legal doctrines. The findings indicate that notaries play a crucial preventive and educational role through their authority to provide legal counseling to ensure that companies understand their CSR obligations from the establishment stage. However, the legal responsibility for CSR implementation lies entirely with the company as an independent legal entity. Notaries cannot be held liable for a company’s failure to fulfill CSR obligations unless proven to have violated the provisions of the Notary Office Law (UUJN) or ethical provisions related to their official duties in preparing authentic deeds.